Development of Antibiotic Resistance, Suggestion For The Safety of Our Future Generation - Mallik, Ashraf Uddin; Rahman, Md Mostafizur; Razzaque, Md Abdur; Karmaker, Uttam; Samad, Abdus; Nasrin, Jannate Sultana; Saha, Simanta; Saha, Simanta; Begum, Rokeya (KYAMC Journal, 2021)
Background: Rising of multidrug resistance among uropathogenic bacteria is leading our future generation to a crisis. Nevertheless, the era of antibiotic failure due to bacterial resistance has brought interest to other medical science like Traditional Medicine, alternative medicine. Objectives: This study was undertaken to determine the current antibiotic resistance situation among common bacterial uropathogens and suggesting prevention measure. Materials and Methods: A total of 212 patients male 132,female 80 selected. Mid-urine samples were collected. Isolated organisms were identified by conventional methods. Then different antibiotics representing different families of antibiotics were tested on isolated organisms. Results: The most frequently isolated gram negative bacteria was E.Coli (92%) followed by Staphylococcus(7.07%),Klebsiella(7%), Pseudomonas(4.25%). Resistance to Amoxicilline, Ciprofloxacin, Cefixim, Ceftriaxone, Cefuroxim, Cefradin, Cefotaxim was more than 70% of all isolates of E.Coli stains. There was relatively low resistance rate to Nitrofurantoin, Gentamycin,Imipenem, Meropenem, Amikacin, Ceftazidim . However, there was emerging resistance to Ciprofloxacin, specially for common bacteria. Conclusion: It is urgent need to make a policy for antibiotics use . We suggest all health care professional of traditional medicine and modern medicine to combat against antibiotics resistance. KYAMC Journal.2021;12(1): 32-35